Risk evaluation of accumulated heavy metals in Radish (Raphanus sativus L. var. sativus) cultivars irrigated by varying water resources - Abdel, Caser Ghaafar; Ibrahim, Aveen A. (Journal of Kerbala for Agricultural Sciences, 2018)
Abstract Three radish cultivars namely Ufasic, Gigante, and Saxa2 grown under plastic house, irrigated by Life bottled drinking water, well and Dohuk River mixed with wastewater to evaluate the risk of accumulated heavy metals in leaves and root of three radish cultivars. Very high amount of Pb accumulated in radish as compared to the international recommended standard (over 0.2 mg/kg). Particularly, in edible leaves of radish irrigated with life bottled water, and wastewater (19.8641 and 15.6603 µg.g-1, respectively). Similar trend of accumulated Pb in edible roots irrigated by bottled water (19.69µg.g-1), and by river mixed with wastewater (25.74µg.g-1). Wastewater significantly increased the accumulated Zn (9.732 µg.g-1), in edible leaves of radish. Radish roots were not capable to sequestered Zn in their roots, and therefore, most absorbed Zn was translocated to leaves. The lowest accumulated Cd in edible roots (0.986μg.g-1) observed in radish irrigated with well water. Saxa2 can be recommended for Pb bio remedy for extracting Pb from growing media. Ufasic and Saxa2 can be recommended for Zn extraction from growing media. Gigante engages the gap between them.